TRANSFORMACE AREÁLU PILY V OBCI BÍLÁ V BESKYDECH - Vrzgula, Lukáš (Vysoké učení technické v Brně. Fakulta architektury)
Diplomová práce se zabývá transformací bývalého areálu pily nacházejícího se v centru obce Bílá v Beskydech. Návrh řeší postupné začlenění areálu do struktury rozvoje lyžařského střediska.

The thesis deals with the transformation of the former sawmill located in the center of the village of Bílá in Beskydy. The proposal addresses the gradual integration of the complex into the ski resort development structure.
TRANSFORMATION OF THE SAWMILL SITE IN MUNICIPALITY OF BÍLÁ IN THE BESKYDY
Keywords: lyžařský areál; lyžování; pila; trasformace; brownfield; Bílá; Beskydy; vesnice; urbanismus; skiing resort; skiing; sawmill; transformation; brownfield; Bílá; Beskydy; village; urbanism